2019
DOI: 10.1155/2019/2723491
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Sensitivity before and after Silicone Oil Removal Using Microperimetry

Abstract: The purpose of the study is to assess the retinal sensitivity, using microperimetry, before and after silicone removal. It included 22 patients admitted for silicone removal after vitrectomy for macula-off retinal detachment. Patients were divided into 2 groups according to the duration of silicone tamponade: Group A: <3 months (included 10 patients), and Group B: 3–6 months (included 12 patients). Retinal sensitivity was tested, using microperimetry, one day before and one month after silicone removal. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, the further surgery required to remove the silicon oil could have biased the outcome for the indication of CES. On the one hand, the fluid exchanges in the vitreous cavity may promote cataract progression; on the other hand, the removal of silicone oil is known to improve retinal sensitivity and, to some extent, visual acuity 19 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the further surgery required to remove the silicon oil could have biased the outcome for the indication of CES. On the one hand, the fluid exchanges in the vitreous cavity may promote cataract progression; on the other hand, the removal of silicone oil is known to improve retinal sensitivity and, to some extent, visual acuity 19 .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Nassar et al (2019) also reported that 6 months or >6 months of SO application affected BCVA. In a recent macula-on retinal detachment study, higher IOP during SO endotamponade was the biggest risk factor for vision loss [ 30 ]. Abu Al Naga et al (2019) and Ghada et al (2019) reported that BCVA improves by 1.06–2.1-fold 4 weeks after removal ( p < 0.05), and the mean IOP before and after 4 weeks of removal were 20.18 mmHg and 14.18 mmHg ( p = 0.025) [ 31 ].…”
Section: Discussionmentioning
confidence: 99%